2019
DOI: 10.1007/s12639-019-01086-7
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and prevalence of ticks on livestock population in endemic area of Kyasanur forest disease in Western Ghats of Kerala, South India

Abstract: Tick borne zoonotic diseases are one of the major emerging threats to live stock and public health in India, especially in Western Ghats of south India. Since livestock and wild animals share habitats and grasslands, it is important to know the species composition of major tick parasitism on live stock as well as their geographical distribution for effective control of tick and tick borne diseases. This study provides basic knowledge that is necessary to initiate Kyasanur Forest Disease (KFD) prevention progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…have not yet been incriminated in the KFDV transmission cycle [32,33]. Hence, cattle may act both as an ampli er of tick numbers and as a disperser of ticks between habitats.…”
Section: Preventing Tick Spread By Cattle Through Protective Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…have not yet been incriminated in the KFDV transmission cycle [32,33]. Hence, cattle may act both as an ampli er of tick numbers and as a disperser of ticks between habitats.…”
Section: Preventing Tick Spread By Cattle Through Protective Measuresmentioning
confidence: 99%
“…Monkeys, principally the black-footed grey langur (Semnopithecus hypoleucos) and the bonnet macaque (Macaca radiata), are thought to act as amplifying hosts, by infecting large numbers of larval ticks with the virus [29]. Cattle do not amplify KFDV since they do not develop viraemia of long duration [30,31], but are hypothesised to amplify tick population density through their importance as a blood meal host [32,33]. The lack of robust testing of these latter two hypotheses in the eld, is indicative of the signi cant gaps in our empirical knowledge of the ecology of the KFDV system.…”
Section: Introductionmentioning
confidence: 99%
“…Collection plays an integral role for the surveillance of vectors to determine the dominant species according to different hosts and seasons, thus yielding detailed knowledge on the occurrence of different vector-borne diseases. Hyalomma anatolicum, Hyalomma marginatum isacci, Rhipicephalus microplus, and Rhipicephalus haemaphysaloides ticks are widely distributed in almost all states of India 19,20 . However, in a study conducted in Lucknow, Uttar Pradesh, Rh.…”
Section: Identification Of Tick Species Using Taxonomical Keysmentioning
confidence: 99%
“…In the early study by Wang et al, ticks from livestock in Northern Xinjiang were identi ed four genera and seven species [8]. In India, Balasubramanian et al found that 168 of 195 detected cattle were infested by ticks, which comprised 3 genera and 7 species [9]. So far, despite numerous studies focused on ticks, it is a great pity that few studies were undergone about ticks in wild animals, especially in China.…”
mentioning
confidence: 99%
“…Cerdena et al found A. parvitarsum-a hard tick on the liolaemus lizards in Peru for the rst time [11]. Additional, as wild animals commonly share the same habitats with domestic animals and human beings, tick-associated agents carried by wild-animals might infect domestic animals and eventually result in human infections [9,12]. Xinjiang, a province with developed animal husbandry [13] and have lizards widely distributed.…”
mentioning
confidence: 99%